SYNERGISTIC CORROSION INHIBITION ACTIVITY OF THE CHICORIUMINTYBUS EXTRACT AND IODIDE IONS FOR MILD STEEL IN ACIDIC MEDIA - Emad E. El-Katori; Abdel-aziz S. Fouda; Rahma R. Mohamed (Journal of the Chilean Chemical Society, 2020)
Herein, An examination into thecorrosion inhibition of mild steel (MS) in 1.0 M HCl bythe Chicoriumintybus extract as a green inhibitor had been achieved via chemical, electrochemical and morphological measurements. The effect of KI additives on corrosion inhibition efficiency was carriedout using a weight loss method. The results reveal that the Chicoriumintybus extract inhibited the corrosion reaction by adsorption onto the metal/solution interface. Inhibition efficiency, increased with the Chicoriumintybus concentration and synergistically increased with the presence of KI. The addition of iodide ions to the Chicoriumintybus extract raises inhibition efficiency of 74 to 99%. Polarization data suggest that the Chicoriumintybus extract acts as a mixed inhibition-mechanism. This observation was further corroborated by the fit of experimental adsorption data to the Temkin isotherm. The results were confirmed by AFM, SEM images and ATR-IR for the surface morphology.